EDUCAÇÃO NÃO-FORMAL E O MOVIMENTO METODISTA: UMA DISCUSSÃO A PARTIR DA ESCOLA DOMINICAL! - Moraes, Rute Bertoldo Vieira (2012)
Our research s goal was to investigate the contribution non-formal education has for formal education in the Methodist Church s Sunday School. Our theoretical framework is based in authors that study non-formal education: Afonso (2002), Simson (2001), Brandão (2002), Duran (2007), Delors (2002), Gadotti (2005), Libâneo (2005) and Gohn (2001). Non-formal education was problematized in the context of Sunday School, grounded on historical evidence from its beginnings in seventeenth century England, its foundation on the methodist movement and in its founder s biography. We considered the contributions provided by Buyers (1929/1945), Heitzenrater (2006), Reily (1991) and Lelièvre (1997). The empirical qualitative research consisted in intensive interviewing and the emplyment of questionnaires. We interviewed a honorary Methodist Bishop, whose life story is ties to the Sunday School environment and the formation it provided as well as its contribution for his choosing of a profession. The questionnaires we elaborated were sent to the communities that attend Sunday School, and were answered by twenty-two people. The analysis of the answers given took into account the contextual conditions in which the interviewees were involved. The results thus gathered raise some questions, because the environment in which Sunday School was first proposed whithin the Methodist Movement is vastly different from the context in which the same practice is carried out nowadays, thus showing the great difficulty Sunday School has in remaining attractive in the modern world that offers many options when it comes to leisure, culture and education. This is in stark contrast to the seventeenth century, when education was a privilege given to very few. Despite this challenge, Sunday School and the non-formal education it provides nowadays are seen by its participants as fundamental in character formation, both spiritually and morally, and relevant for society as a whole.